25.2k views
2 votes
X/3-2=3(x+2) i need help solving it please

1 Answer

2 votes

Given equation is


x

--------- - 2 = 3 ( x + 2)

3


This is an equation .

The first term at left side of the equation is in fraction .

First step is to get rid of the fraction .

We have 3 in denominator . To get rid of fraction , we multiply the whole

equation by 3 .

We multiply each term by 3 .

x * 3

----- - 2 * 3 = 3 * 3 ( x + 2 )

3

Simplifying we get

x - 6 = 9 ( x + 2 )

Distribute 9 inside the parenthesis , we get

x - 6 = 9 x + 9 * 2

x - 6 = 9 x + 18

Now we need to combine like terms .

Adding 6 both sides we get

x - 6 + 6 = 9 x + 18 + 6

x = 9 x + 24

Subtract 9 x from both sides , we get

x - 9 x = 24

- 8 x = 24

Divide by - 8 , we get

x = - 24/8

x = - 3 .

Thus the solution of the given equation is x = - 3 .

User Rstrelba
by
5.5k points